Diritto, magia e performatività - Viggiani, Giacomo (Rivista Italiana di Filosofia del Linguaggio, 2014)
It is a general belief that rights and duties are something real and existing. When we claim we have a right to do something, we speak as we have a power to do that thing. According to the common opinion, this power consists in the possibility to activate the legal process against the people violating our right. However, the legal process makes the duty mandatory and forces people to respect my right, but their conscience will not feel the duty as obligatory. At the same time, I believe that I have a right before activating the legal process, which only enforces a right that I already have. What are these rights and duties then? The paper explores the solution suggested by Scandinavian realism, which claims that binding power of the law derives from ancestral faith in the power of verbal magic.